Preparation and applications of wettability-controlled fluoroalkyl end-capped oligomer/cellulose nanofiber composites. (March 2021) - Sawada, Hideo; Endo, Yui; Oikawa, Yuri
Sol-gel reaction of two fluoroalkyl end-capped vinyltrimethoxysilane oligomer [RF -(CH2 CHSi(OMe)3 ) n -RF ; RF = CF(CF3 )OC3 F7 ; n = 2, 3: RF -(VM) n -RF ] in the presence of cellulose nanofiber (CNF) under non-catalytic conditions was found to provide the corresponding fluorinated oligomeric silica/CNF composites [RF -(VM-SiO3/2 ) n -RF /CNF]. The obtained composites were applied to the surface modification of glass to give a good oleophobic/superhydrophobic characteristic on the composite surface due to the fabrication of the roughness architecture. The RF -(VM-SiO3/2 ) n -RF /CNF composites were also applied to the surface modification of poly(ethylene terephthalate) [PET] fabric swatch, affording a superoleophilic/superhydrophobic characteristic on the modified fabric surface. Modified PET fabric swatch thus obtained was applicable to not only the separation membrane to separate the mixture of oil/water but also the perfect adsorption of oil droplets spread on water interface. In addition, we have prepared the RF -(VM-SiO3/2 ) n -RF /CNF composites films by casting homogeneous aqueous methanol solutions containing the corresponding composites. Pristine CNF film afforded the superoleophilic property on the surface; however, it was demonstrated that the obtained transparent colorless CNF composite films can supply highly oleophobic characteristic on the surface.